2010
DOI: 10.1634/theoncologist.2009-0153
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Phase III Clinical Trial of Five Different Arms of Treatment in 332 Patients with Cancer Cachexia

Abstract: Purpose. A phase III, randomized study was carried out to establish the most effective and safest treatment to improve the primary endpoints of cancer cachexia-lean body mass (LBM), resting energy expenditure (REE), and fatigue-and relevant secondary endpoints: appetite, quality of life, grip strength, Glasgow Prognostic Score (GPS) and proinflammatory cytokines.Patients and Methods. Three hundred thirty-two assessable patients with cancer-related anorexia/cachexia syndrome were randomly assigned to one of fiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
224
0
4

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 203 publications
(229 citation statements)
references
References 61 publications
1
224
0
4
Order By: Relevance
“…In particular, multimodal trials have been recommended; however, the majority of cachexia trials have used single agents in isolation, or have lacked a comparator arm 23, 24. Where multimodal trials have been done,25, 26, 27 these have examined two or more components, and whilst some findings have been encouraging, to date, there have been no randomised trials integrating all the components we consider to be appropriate and this has resulted in a failure to advance cachexia treatment 28. Our findings suggest that multimodal cachexia intervention is safe and feasible and support further examination of this approach to fully assess effects on weight and lean body mass in larger trials.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, multimodal trials have been recommended; however, the majority of cachexia trials have used single agents in isolation, or have lacked a comparator arm 23, 24. Where multimodal trials have been done,25, 26, 27 these have examined two or more components, and whilst some findings have been encouraging, to date, there have been no randomised trials integrating all the components we consider to be appropriate and this has resulted in a failure to advance cachexia treatment 28. Our findings suggest that multimodal cachexia intervention is safe and feasible and support further examination of this approach to fully assess effects on weight and lean body mass in larger trials.…”
Section: Discussionmentioning
confidence: 99%
“…Compared with prior studies, 4,7,13,15 this is the first to investigate the effect of thalidomide and placebo using validated ACS measures and cytokines. However compared with prior studies, our sample size was smaller, we had a high rate of the attrition, and noncompliance rates were higher.…”
Section: Discussionmentioning
confidence: 99%
“…[4][5][6] Various treatments have been investigated for ACS; however, they were found to be of limited efficacy in improving ACS. 2,5,7 There has been renewed interest in the use of thalidomide for ACS. 7 This interest is based on previous studies using thalidomide for the treatment of acquired immunodeficiency syndrome (AIDS)-associated cachexia 8 and the effects of thalidomide in modulating the release of cytokines such as tumor necrosis factor (TNF)-a and interleukin (IL)-10.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients with metastatic cancer receiving thalidomide showed improvement of quality of life (Bruera et al, 1999), weight loss (Khan et al, 2003, Gordon et al, 2005, lean body mass and physical functions (Gordon et al, 2005). Finally, a large randomised trial including cachectic cancer patients showed that thalidomide alone is less effective that its combination with other treatments (Mantovani, 2010). More recently an experimental study reported that thalidomide inhibits an E3 ubiquitin ligase complex involved in embryonal development (Ito et al, 2010), leading to hypothesize that thalidomide effectiveness on muscle wasting in cancer hosts could be achieved through inhibition of muscle-specific ubiquitin ligases.…”
Section: Inhibition Of Cytokine Productionmentioning
confidence: 99%